MiR-210-3p attenuates lipid accumulation and inflammation in atherosclerosis by repressing IGF2. Issue 2 (1st February 2020) - Qiao, Xiang-Rui; Wang, Liang; Liu, Mengping; Tian, Yuling; Chen, Tao
ABSTRACT: Previous studies have shown that miR-210-3p is involved in the development and progression of atherosclerosis, but its specific mechanisms are still unclear. This study aims to reveal the mechanism of miR-210-3p and its target genes in macrophage lipid deposition and inflammatory response, and provide new ideas for the treatment of atherosclerosis. We found miR-210-3p increased sharply in the first 12 h induced by higher doses of ox-LDL in THP-1 macrophages and then gradually decreased. MiR-210-3p mimic transfection inhibited lipid uptake and inflammatory cytokine production in ox-LDL-induced macrophages. By inhibiting IGF2/IGF2R, miR-210-3p suppressed the expression of fatty acid transcriptase CD36 and transcription factor NF-κB in ox-LDL-induced macrophages. In conclusion, miR-210-3p inhibits the expression of CD36 and NF-κB by inhibiting IGF2 / IGF2R, thereby reducing lipid accumulation and inflammatory response in ox-LDL-induced macrophages. Enhancing miR-210-3p expression may be a new strategy for the treatment of atherosclerosis. Graphical abstract: : MiR-210-3p attenuates the expression NF-κB and CD36 by binding to 3ʹUTR of human IGF2, and then suppresses lipid